On the nature of shocks driving exchange rates in emerging economies - Galina V. Kolev (FIW - Research Centre International Economics, 2015)
The paper analyzes the sources of exchange rate movements in emerging economies in the context of monetary tapering by the Federal Reserve. A structural vector autoregression framework with a long-run restriction is used to decompose the movements of nominal ex-change rates into two components: one component driven solely by the adjustment of the real exchange rate to permanent shocks and one resulting from transitory shocks such as monetary policy measures. Imposing the restriction that temporary shocks should not affect the real exchange rate in the long run, the analysis shows that the recent depreciation of the Russian ruble and the Turkish lira is largely driven by transitory shocks, like for instance monetary policy measures. Furthermore, the response of the lira to transitory shocks is sluggish and further depreciation is possible in the next months. In Brazil and India, on the contrary, nominal exchange rate behavior is mainly driven by permanent shocks. The recent depreciation is not caused by short-lived shocks but rather by changing long-term macroeconomic fundamentals. The foreign exchange interventions of the central bank to avoid large depreciation are therefore largely misplaced, especially in Brazil. They aggravate the use of nominal exchange rate flexibility as an efficient adjustment mechanism for real exchange rate changes, i.e. changes in relative prices across borders, and efficient allocation of resources.
Keywords: F31; E58; 330; Exchange rates; emerging economies; SVAR; monetary policy